3(x+8)+3=5(x-2)-4x+9

Simple and best practice solution for 3(x+8)+3=5(x-2)-4x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+8)+3=5(x-2)-4x+9 equation:



3(x+8)+3=5(x-2)-4x+9
We move all terms to the left:
3(x+8)+3-(5(x-2)-4x+9)=0
We multiply parentheses
3x-(5(x-2)-4x+9)+24+3=0
We calculate terms in parentheses: -(5(x-2)-4x+9), so:
5(x-2)-4x+9
We add all the numbers together, and all the variables
-4x+5(x-2)+9
We multiply parentheses
-4x+5x-10+9
We add all the numbers together, and all the variables
x-1
Back to the equation:
-(x-1)
We add all the numbers together, and all the variables
3x-(x-1)+27=0
We get rid of parentheses
3x-x+1+27=0
We add all the numbers together, and all the variables
2x+28=0
We move all terms containing x to the left, all other terms to the right
2x=-28
x=-28/2
x=-14

See similar equations:

| (5p+3)^2=8 | | 6–7p=-9p | | 9x-8x+3=-6 | | -2=3x+4=13 | | x+42+37=180 | | -2=-6/7x+10 | | 5(x-3+6=4x+3 | | x-157-12x=85 | | 2=-4+3v | | -8+v/2=4 | | x+9=5x+11 | | 40(x+3)-20=18 | | 7+5u=2 | | 10/40=50/x | | b-1=5b-8+3b;b | | 5/6=x-5/x-3 | | 2(4f-3)-8=4+2f;f | | 1+a÷-9-4=0 | | 2/5x+1/3=7x-2/15 | | 7n-4(n+8)=3(n+3) | | 3/4x-3=2/5 | | X^2=6x+1=0 | | -5(1-5e)+5(-8e-2)=-4e-8e;e | | 14=-(g-8);g | | 6y^2-48=3y^2 | | 40n=30n+200 | | 16=-4(-c+1);c | | 5x+6=49+57 | | 5d+34=-2(1-7d)d | | 5d+34=-2(1-7d); | | |w|+8=17 | | 5d+34=-2(1-7d);d |

Equations solver categories